Factors associated with patients who prefer HIV self-testing over health professional testing in an emergency department-based rapid HIV screening program. (October 2017) - Hsieh, Yu-Hsiang; Beck, Kaylin J; Rothman, Richard E; Gauvey-Kern, Megan; Woodfield, Alonzo; Peterson, Stephen; Signer, Danielle; Gaydos, Charlotte A
Kiosk-facilitated HIV self-testing has been shown to be accurate and well accepted by emergency department (ED) patients. We investigated factors associated with patients who preferred self-testing over testing performed by health professionals in an ED-based HIV screening program. This opt-in program evaluation studied 332 patients in an inner-city academic ED from February 2012 to April 2012, when a kiosk-based HIV self-testing program was standard of care. The first kiosk in the 2-stage system registered patients and assessed their interest in screening, while the second kiosk gathered demographic and risk factor information and also provided self-testing instructions. Patients who declined to self-test were offered testing by staff. Broad eligibility included patients aged 18–64 years who were not critically ill, English-speaking, able to provide informed consent, and registered during HIV program operational hours. Data were analyzed using descriptive statistical analysis and Chi squared tests; 160 (48.2%) of 332 patients consenting to testing chose to use a kiosk to guide them performing self-testing. Patients aged 25–29 years and those whose primary ED diagnosis was not infectious disease-related were more likely to prefer HIV self-testing (OR = 2.19, 95% CI: 1.17–4.10; OR = 1.79, 95% CI: 1.03–3.12). HIV self-testing in the ED could serve as a complementary testing approach to the conventional modality.